Do Class Closures Affect Students' Achievements? Heterogeneous Effects of Students' Socioeconomic Backgrounds - Masato Oikawa; Ryuichi Tanaka; Shun-ichiro Bessho; Akira Kawamura; Haruko Noguchi (Institute of Labor Economics (IZA), 2022)
This paper examines how class closures affect the academic achievements of Japanese students in primary and middle schools, with a special focus on the heterogeneous effects of the socioeconomic backgrounds of students' households. Utilizing the administrative data of students from a city in the Tokyo Metropolitan Area, we estimated the effects of class closures due to flu epidemics, on the students' language and math test scores. We find that class closures adversely affect math test scores of economically disadvantaged students. The magnitudes of the negative effects on disadvantaged students are heterogeneous by subject, grade in school, gender, timing of class closures, and students' achievements at the beginning of the school year. Male students from economically disadvantaged households are more susceptible to class closures, and those with relatively low achievements before class closures suffer more seriously from them. The deleterious effects among economically disadvantaged male students are driven not only by reductions in class hours in school, but also by increases in time spent watching TV and playing video games. We also find that school resources can mitigate the negative impact of class closure among economically disadvantaged students. These results indicate the importance of public programs in preventing a negative temporal shock to student learning environments.
Keywords: I20; I24; 330; students' usage of time; students' achievements; flu epidemic; class closures; instruction time